Pengaruh Pemberian Blanket Warmer Terhadap Kejadian Shivering Pasca Operasi Sectio Caesarea Pada Pasien Spinal Anastesi di Recovery Room RSUD dr. Soedomo Trenggalek - Lurru Erawanjie, Adelia; Budiono; Marsaid; Supono (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Objective: to determine the effect of blanket warmer on the incidence of shivering after sectio caesarea surgery in spinal anesthesia patients in the recovery room. Metods:This research used quasi experimental with Two Group Pretest-Posttest Design. The population in this study were all sectio caesarea patients with spinal anesthesia at RSUD Dr. Soedomo Trenggalek with the incidence of shivering with a total sample of 36 people, using accidental sampling. Results: The study using the Wilcoxon test in the intervention group obtained the results (p = 0.000), meaning that there was an effect of giving blanket warmers on the incidence of shivering after cesarean section surgery with spinal anesthesia. While the results of the Wilcoxon test on the control group obtained the results (p = 0.001), meaning that there is a significant difference between the results of the pre-test and post-test in the control group. Based on the results of the Mann Whitney test, the value (p = 0.000) was obtained, meaning that there was an effect of giving blanket warmers on the incidence of shivering after cesarean section surgery with spinal anesthesia. Conclusion: The provision of blanket warmer was found to have an effect in reducing the degree of shivering.